The Cognitive and Behavioural Impact of Alcohol Promoting and Alcohol Warning Advertisements: An Experimental Study. - Brown, Kyle G.; Stautz, Kaidy; Hollands, Gareth J.; Winpenny, Eleanor M.; Marteau, Theresa M. (Alcohol & Alcoholism, 2016)
To assess the immediate effect of alcohol promoting and alcohol warning advertisements on implicit and explicit attitudes towards alcohol and on alcohol seeking behaviour.~Aims~Objective~We conducted a between-participants online experiment in which participants were randomly assigned to view one of three sets of advertisements: (a) alcohol promoting, (b) alcohol warning, or (c) unrelated to alcohol. A total of 373 participants (59.5% female) aged 18-40 (M = 28.03) living in the UK were recruited online through a research agency. Positive and negative implicit attitudes and explicit attitudes towards alcohol were assessed before and after advertisements were viewed. Alcohol seeking behaviour was measured by participants' choice of either an alcohol-related or non-alcohol-related voucher offered ostensibly as a reward for participation. Self-reported past week alcohol consumption was also recorded.~Methods~Methods~There were no main effects on any of the outcome measures. In heavier drinkers, viewing alcohol promoting advertisements increased positive implicit attitudes (standardized beta = 0.15, P = 0.04) and decreased negative implicit attitudes (standardized beta = -0.17, P = 0.02). In heavier drinkers, viewing alcohol warning advertisements decreased negative implicit attitudes (standardized beta = -0.19, P = 0.01).~Results~Results~Viewing alcohol promoting advertisements has a cognitive impact on heavier drinkers, increasing positive and reducing negative implicit attitudes towards alcohol. Viewing alcohol warning advertisements reduces negative implicit attitudes towards alcohol in heavier drinkers, suggestive of a reactance effect.~Conclusions~Conclusions